PAGET’S DISEASE OF THE BREAST: STUDY OF CASES SERIES - Eulálio Filho, Walberto Monteiro Neiva; Esteves, Flávia Vanessa Carvalho Sousa; Fé, Taíla Sousa de Moura; Furtado, Luan Barbosa; Silva Junior, Raimundo Gerônimo da; Vieira, Sabas Carlos (Mastology, 2017)
Objective: To evaluate the survival of a series of patients with Paget’s disease of the breast. Methods: Observational, retrospective and descriptive study. Data were collected through electronic medical records; the following variables were obtained: age, tumor histology, tumor size, degree of differentiation, lymphatic invasion, vascular invasion, neural invasion, presence or not of potential involvement of axillary lymph nodes, immunohistochemical profile, treatments performed, recurrence, and follow-up. Results: Of the 301 cases of assisted breast cancer, six patients were identified with Paget’s disease of the breast. The overall survival, with a mean follow-up of 54 months, was 100%. All individuals are free of disease activity. The most common histochemical profile was negative for estrogen and progesterone receptors, and positive for HER-2/neu. Axillary and/or distal metastatic involvement was not identified. Conclusions: Overall survival was 100%, with a mean follow-up of 54 months. This high rate is due to the absence of axillary and/or distal metastatic involvement in our series.